An intact Raf zinc finger is required for optimal binding to processed Ras and for ras-dependent Raf activation in situ. - Luo, Z (1997)
The function of the c-Raf-1 zinc finger domain in the activation of the Raf kinase was examined by the creation of variant zinc finger structures. Mutation of Raf Cys 165 and Cys 168 to Ser strongly inhibits the Ras-dependent activation of c-Raf-1 by epidermal growth factor (EGF). Deletion of the Raf zinc finger and replacement with a homologous zinc finger from protein kinase C gamma (PKC gamma) (to give gamma/Raf) also abrogates EGF-induced activation but enables a vigorous phorbol myristate acetate (PMA)-induced activation. PMA activation of gamma/Raf does not require endogenous Ras or PKCs and probably occurs through a PMA-induced recruitment of gamma/Raf to the plasma membrane. The impaired ability of EGF to activate the Raf zinc finger variants in situ is attributable, at least in part, to a major decrement in their binding to Ras-GTP; both Raf zinc finger variants exhibit decreased association with Ras (V12) in situ upon coexpression in COS cells, as well as diminished binding in vitro to immobilized, processed COS recombinant Ras(V12)-GTP. In contrast, Raf binding to unprocessed COS or prokaryotic recombinant Ras-GTP is unaffected by Raf zinc finger mutation. Thus, the Raf zinc finger contributes an important component to the overall binding to Ras-GTP in situ, through an interaction between the zinc finger and an epitope on Ras, distinct from the effector loop, that is present only on prenylated Ras.